Spray characteristics of Al-nanoparticle-containing nanofluid fuel in a self-excited oscillation injector. (15th April 2021) - Jia, Bo-qi; Fu, Qing-fei; Xu, Xu; Yang, Li-jun; Zhang, Ding-wei; Wang, Tie-han; Wang, Qun
Highlights: The spray characteristics of nano-particle containing liquid fuel are investigated. The self-excited oscillating injector is used to atomize the fuel. For the self-excited oscillating injector, the mean diameter and drop size. Distribution is more satisfactory than that of the directly current injector. Abstract: To promote fuel density and energy, energetic nanoparticles (NPs) are added to fuels, however, the non-Newtonian feature of NPs containing suspension restricts their application in the aerospace field. Self-excited oscillation is an effective way to improve the oscillations of the liquid jet, and may contribute to atomization. A set of spray systems were established in this study to investigate the spray characteristics of NP suspension in a self-excited oscillation (SEO) injector. To change the resonance feature of the injectors, eight SEO injectors with different structure parameters were constructed, and a direct current (DC) injector was designed for comparison with the SEO injectors. The rheological behavior of the fuel was tested, and its spray characteristics investigated. Details of the spray field were recorded using a high speed camera, and the effects of these geometrical parameters on discharge coefficient, droplet size distribution, and Sauter mean diameter (SMD) were obtained, as well as an optimum structure parameter of the injector.